The Star, 26 March 2007 - Jessy, Kuldeep S. (The Star (Malaysia), 2007)
The Polis DiRaja Malaysia has undergone numerous transformations from the time it was set up 200 years ago and it is contanstly changing, to be current and of service to the people. Deputy Inspector-General of Police Datuk Mohd Najib Abdul Aziz speaks about the future.